Leveraging Digitality for SME Internationalization and Business Model Innovation - Bouwman, Harry; Meroño, Angel; Heikkilä, Marikka; Eriksson, Taina (De Gruyter, 2025)
Small and medium-sized enterprises (SMEs) are constantly looking for opportunities for growth, at home and abroad. While changing a few components of a business model (BM) may be enough to realize local growth, international expansion may require more radical BM changes. This paper takes an explorative approach to analyze the implications of the entrepreneurial SME's internationalization strategy to BM innovation (BMI). Specifically, we consider the role of digital transformation. As such, this study contributes to existing literature on: (1) international management, (2) digitaliza-tion, and (3) BMI experimentation and outcome. We carry out a multiple case study using a theoretical sampling approach based on two explanatory factors: (1) the maturity of the SME, that is, established firm versus start-up and (2) the use of IT, that is, web-based channels versus digital platforms. The study shows how internationalization led to different types of changes in the BM. It also shows how digitalization can help in entering into new international markets. Digital platforms provide great potential for internationalization for SMEs but require changes impacting most BM components, such as redesign of value proposition and development of local ecosystems. To date, few studies have looked at IT platforms as a way to enter international markets. Platform based BMI requires the development of local ecosystems.
De Gruyter Handbook of Digital Entrepreneurship